Dilema Implementasi Kurikulum Merdeka: Menyasar Pembelajaran atau Karakter? - Nihayah, Risa Wardatun; Dina, Wahyu Farrah; Wijayanti, Dyana; Asyah, Annabel Noor (Pusat Standar dan Kebijakan Pendidikan, BSKAP, Kemendikbudristek, 2023)
This research seeks to understand how a curriculum reform that emphasizes studentcentered learning influences classroom instruction. The new curriculum is designed by the government of Indonesia to grant autonomy to teachers in re-emphasizing learning according to the student’s needs and local context. Previous studies suggest that teacher autonomy in elaborating curricula and pedagogy is associated with student’s engagement and improvement in learning outcomes. Given the low autonomy of teachers in Indonesia, their responses can inform how we should formulate effective reforms. This research used a case study to investigate how curriculum reform is perceived by middle school teachers and how they translate it into classroom instruction. The data was collected through classroom observations and complemented by semi-structured phone interviews with 20 Math teachers in Jakarta and Central Java from November 2022 to February 2023. To avoid incongruous instruction, this research informs that countries with a long history of low teacher autonomy like Indonesia should not promote a grand education reform design without clear guidelines and adequate support. The reformers need to touch upon teacher’s beliefs about curriculum completion and didactic pedagogy before expecting them to change their teaching practices into active learning and exercise their authority in independently developing curricula.